The Influence of the Help of the Smart Indonesia Collage Card (KIPK) on the Motivation of Student Studying at the Faculty of Economics & Business, State University of Jakarta - Azizah, Nur; Marsofiyati, Marsofiyati; Utari, Eka Dewi (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to analyze the effect of Indonesia Smart College Card (KIP-K) assistance on student motivation to study at the Faculty of Economics and Business, State University of Jakarta. KIP-K as an educational assistance program from the government is expected not only to ease the financial burden, but also to increase motivation both intrinsically and extrinsically. The research method used is descriptive quantitative with a survey approach through a questionnaire to 84 respondents who are KIP-K recipients. The regression analysis results show that there is a positive and significant influence between KIP-K assistance and student learning motivation, with a significance value of 0.000 (<0.05) and a coefficient of determination of 24.6%. This finding reinforces that financial support can be a driver of enthusiasm for learning, both from within students (intrinsic motivation) and due to external factors such as family expectations and rewards (extrinsic motivation). This study recommends that the KIP-K program should continue to be developed, not only in terms of financial assistance, but also with approaches that encourage the growth of sustainable learning motivation.